0636 Activity-Rest Patterns and Symptoms in Inflammatory Bowel Disease. (12th April 2019) - Conley, Samantha; Jeon, Sangchoon; Lehner, Vanesssa; Proctor, Deborah D; Redeker, Nancy S
Abstract: Introduction: Inflammatory bowel disease (IBD) is a chronic disease that follows an unpredictable course of active disease and remission. Sixty-percent of individuals with IBD experience co-occurring pain, fatigue, and sleep disturbance. These symptoms persist during remission, but little is known about their etiology in IBD. The purpose of this study was to describe the associations between activity-rest rhythms and symptoms in adults with IBD in remission. Methods: We conducted a 10-day study of adults 18 to 60 with IBD in remission. We measured activity-rest patterns for 10 days with wrist actigraphy (Phillips Respironics Spectrum); symptoms of fatigue, pain, mood, and sleep disturbance were measured twice daily for 10 days with visual analog scales (0-100) and depression and anxiety at baseline with PROMIS scales. We collected salivary melatonin once at habitual bedtime. Symptom burden was defined as low (0 to 1 symptoms) or moderate-high symptom group (2 or more symptoms). Activity-rest data were analyzed with cosinor (mesor, amplitude, acrophase, circadian quotient) and non-parametric methods (interdaily stability, intradaily variability). Descriptive, t-tests, and effect size (Cohen's d) statistics were used. Results: Of the 23 study participants [age M = 36.0 years (SD 12.6), 13 (56.5%) female, 11 (78.6%) white], 13 (56.5%) had Crohn's disease. Among the six people belonging to the low symptom group, 33% were female, and were 3.86 years younger than the moderate-high symptom group. There were moderate, nonsignificant associations between interdaily stability (mean difference = .214, p = .143, d = .739), bedtime melatonin (mean difference -6.55pg/ml, p = .380, d = .628), acrophase (mean difference = 30 minutes, p = .375, d = .404) and symptom group membership. The moderate-high symptom group had lower interdaily stability, higher bedtime melatonin, and earlier acrophases than the low symptom group. Conclusion: People with IBD may benefit from interventions, such as bright light therapy, to improve stability in their circadian rhythms, which in turn may improve their symptoms during remission. Research is needed to expand these findings in larger samples and explore these relationships longitudinally. Support (If Any): Eastern Nurses Foundation American Nurses Foundation Scholar